2007
DOI: 10.1210/jc.2006-2509
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Prolonged Orocecal Transit Time and Small Intestinal Bacterial Overgrowth in Acromegalic Patients

Abstract: These data demonstrate for the first time that SIBO occurs more frequently in acromegalic patients, however, it can be successfully treated by a specific antibiotic. Medical therapy with somatostatin analogs does not affect SIBO prevalence. OCTT resulted significantly prolonged in both "treated" and "untreated" patients, suggesting that acromegaly determines per se an impairment of the intestinal motility. Indeed, disease control seems irrelevant on the delayed OCTT, suggesting that this alteration might be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 19 publications
0
30
0
3
Order By: Relevance
“…In contrast, a recent Swedish study of 162 IBS patients did not support an important role for SBBO, although mildly increased counts of upper small bowel bacteria were observed in IBS patients compared with 26 healthy controls [20]. A variety of other conditions appear to predispose to SBBO, including cirrhosis [21], cystic fibrosis [22], acromegaly [23], celiac sprue [24], and enterocutaneous fistulae [6].…”
Section: Predisposing Factors For Sbbomentioning
confidence: 96%
“…In contrast, a recent Swedish study of 162 IBS patients did not support an important role for SBBO, although mildly increased counts of upper small bowel bacteria were observed in IBS patients compared with 26 healthy controls [20]. A variety of other conditions appear to predispose to SBBO, including cirrhosis [21], cystic fibrosis [22], acromegaly [23], celiac sprue [24], and enterocutaneous fistulae [6].…”
Section: Predisposing Factors For Sbbomentioning
confidence: 96%
“…Moreover, there are a very limited number of studies focused on gastrointestinal functional disorders in acromegaly, and it has been shown that active acromegaly may induce impairment of the intestinal motility [16]. Resmini et al revealed prolonged oro-cecal transit time and small intestinal bacterial overgrowth in acromegaly patients [5], and Catnach et al found that gall bladder motor function was severely impaired in untreated acromegaly patients [17]. In another study reporting on gall bladder emptying and small intestinal transit in acromegaly patients, Hussaini et al showed that intestinal transit and gall bladder volume were significantly different between acromegaly patients and controls [18].…”
Section: Discussionmentioning
confidence: 99%
“…intestine and colonic transit time, bacterial overgrowth has been demonstrated in acromegaly patients [5,6]. Additionally, previous studies have shown that somatostatin analogues in the treatment of acromegaly could impair gall bladder emptying, which leads to gallstones [7].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Furthermore, patients were treated with rifaximin and 53% obtained eradication of the bacterial overgrowth at follow-up. Moreover, the analysis of symptoms showed that patients with SIBO presented an increased prevalence of intestinal meteorism and flatulence and after eradication therapy; symptoms disappeared from 60% of the treated patients [41].…”
Section: Sibomentioning
confidence: 99%